Analysis Of Dividend Policy With Profitability As Intervening Variable In Financial Sector Companies Listed On The Indonesia Stock Exchange - Ayu Rachmawati; Nurjanti Takarini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The study is done to determine the influence of profitability as an intervening variable in its influence on leverage and the size of the company on the dividends policy. The population of financial sector companies listed in BEI during the year 2018- 2021. The method employed in sample formulating uses a purposive sampling method. We've obtained as many as 24 companies under 4 years of observation, bringing the total data to 96. Using data analysis techniques for path analysis, outlier tests, classic assumption tests, hypothetical and sobel impact detection tests with the help of a SPSS 26 data analysis program. Research suggests that corporate leverage and size do not affect profitability. Leverage has no effect on the dividends policy, corporate size and profitability has no impact on the dividends policy, while profitability as a variable intervening is unable to capitalize on the relationship between leverage and corporate size on the dividends through indirect influence that is greater than direct impact and proving by using the sobel test.